Landasan Politik Dalam Konsep Al-Qur’an: Konsep Kepemimpinan - ariella zaneta (Program Pascasarjana IIQ Jakarta, 2025)
Leadership is inherently linked to the role of a leader, defined as someone who guides others towards shared goals, influenced by principles rooted in Islamic teachings. The Quran characterizes leaders using various terms, emphasizing their dual role as guides and authorities responsible for their followers. Justice (adl), derived from Arabic, encompasses fairness and balance, essential for any leader who must make decisions impartially, such as resolving disputes transparently. Trustworthiness (amanah) is another critical trait, reflecting honesty and responsibility while ensuring community well-being. The practice of consultation (musyawarah) holds significance in Islam for decision-making in both worldly and religious matters. It is essential for participants to possess relevant knowledge for effective discourse. Women are equally entitled to leadership roles based on capability as outlined in the Quran, counteracting historical misconceptions of gender-based leadership restrictions. Divergent views on democracy and consultation among Muslim scholars showcase various perspectives, ranging from identifying similarities between the two systems to outright contradictions. Historical instances of consultation during early Islamic leadership electing successors reveal a participatory aspect in governance. Ultimately, the concepts of leadership in Islam advocate for inclusive practices that promote justice, trust, and community involvement, reflecting the foundational teachings of the Quran. Keywords: leadership, Koran, politics